Single-Ventricle Physiology - Lydia Taranto; Tabitha Moe (US Cardiology Review)
Single-ventricle physiology occurs in patients with hypoplastic ventricular heart defects, either on the right or left, who have undergone stepwise palliation surgeries ending with the Fontan procedure. After Fontan completion, these patients are dependent on passive venous return to the pulmonary circulation. The implications of passive flow are potentially devastating to the patient. We discuss some of the basic changes to the patient’s experience after a Fontan procedure, as well as the common complications. We also touch on some of the emerging management strategies for the common complications.